Prevalence and Features of Thyroglossal Duct Cyst on Ultrasonography, According to Radioactive Iodine Therapy: A Single-Center Study - Park, Ji Sun; Kim, Dong Wook; Shin, Gi Won; Park, Jin Young; Lee, Yoo Jin; Choo, Hye Jung; Park, Ha Kyoung; Ha, Tae Kwun; Kim, Do Hun; Jung, Soo Jin; Moon, Sung Ho; Ahn, Ki Jung; et al. (Frontiers in Endocrinology, 2020)
Objective: The relationship between radioactive iodine therapy (RIT) and prevalence of thyroglossal duct cysts (TGDC) on ultrasonography (US) has not been reported. We assessed the prevalence and US features of TGDC according to RIT. Methods: From July 2017 to June 2018, 3146 subjects underwent thyroid or neck US at our center. The presence or absence of TGDCs was prospectively investigated based on real-time US examination. Among the 3146 subjects, 261 subjects were excluded because of <18 years of age, unclear information of RIT, or the presence of a radiation therapy history to the neck. Eventually, 2885 subjects were included in this study. Results: Of the 2885 subjects finally included, 126 (4.4%) showed a TGDC on US. Those with RIT history showed a higher prevalence of TGDCs than those without (no statistical difference, p = 0.062). In 697 male subjects, there were statistical differences in type of surgery, RIT history, and session number of RIT between those with or without TGDCs (p < 0.0001). In 126 subjects with TGDCs, only sex showed a significant difference between those with or without RIT history (p = 0.015). However, there were no significant differences in the location, size, and shape of TGDCs (p > 0.05). The common US features of TGDC were suprahyoid location, approximately 1 centimeter, and flat-to-ovoid or round shape. Conclusions: RIT may increase the prevalence of TGDCs, particularly in men.